Faktor-faktor Yang Dapat Mencegah Kecenderungan Kecurangan Akuntansi - Lutfi Madani; Meta Arief; Aristanti Widyaningsih (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Cases of fraud in financial statements are rife and increasingly concerning lately. The cases that usually occur are corruption, manipulation, misappropriation of assets and always manage to become the center of attention of all groups and become one of the serious discussions. Accounting fraud is certainly very detrimental and requires real action and action to minimize the potential for fraud. The development of economic research studies shows that fraudulent practices are caused by many factors such as weak internal control, lack of integrity and other factors that result in ethical violations in carrying out their duties. The purpose of this study is to explain how the influence of internal control and the suitability of compensation on the tendency of accounting fraud. This study uses the Systematic Literature Review (SLR) method by reviewing several articles in the form of journals within the last 10 years starting from 2012 to 2022. The results of this study reveal that internal control, compensation suitability has a significant effect on accounting fraud tendencies. This research is expected to add insight and enrich the reader's knowledge about internal control, compensation suitability, and accounting fraud.